NUMERICAL SIMULATION OF HIGH-SPEED IMPАCT RESPONSE OF CARBON ARAMID FIBER COMPOSITES - Pl Jun; CUI HongLi; JIA YuanKun (Jixie qiangdu)
Aiming at the high-speed impact problem of laminates, a three-dimensional finite element impact model consisting of 8 node cohesive element and 8 node solid element is established based on continuous damage mechanies. Based on the Hashin criterion, fiber damage can be well predicted, and puck criterion can well predict matrix damage, therefore. the criterion formed by the mixture of Hashin and puck is compared with the single Hashin failure criterion. It is found that the prediction result of the mixed criterion is closer to the test value. On this basis, the effects of ply angle and impact angle on the impact resistance of laminates are analyzed. The results show that the greater the angle difference between adjacent plies, the greater the incident angle, the stronger the impact resistance of laminates.